Desorption of isopropyl alcohol from adsorbent with non-thermal plasma - Shiau, Chen Han (Environmental technology, 2017)
Effective desorption of isopropyl alcohol (IPA) from adsorbents with non-thermal plasma is developed. In this system, IPA is effectively adsorbed with activated carbon while dielectric barrier discharge is applied to replace the conventional thermal desorption process to achieve good desorption efficiency, making the treatment equipment smaller in size. Various adsorbents including molecular sieves and activated carbon are evaluated for IPA adsorption capacity. The results indicate that BAC has the highest IPA adsorption capacity (280.31 mg IPA/g) under the operating conditions of room temperature, IPA of 400 ppm, and residence time of 0.283 s among 5 adsorbents tested. For the plasma desorption process, the IPA selectivity of 89% is achieved with BAC as N2 is used as desorbing gas. In addition, as air or O2 is used as desorbing gas, the IPA desorption concentration is reduced, because air and O2 plasmas generate active species to oxidize IPA to form acetone, CO2, and even CO. Furthermore, the results of the durability test indicate that the amount of IPA desorbed increases with increasing desorption times and plasma desorption process has a higher energy efficiency if compared with thermal desorption. Overall, this study indicates that non-thermal plasma is a viable process for removing VOCs to regenerate adsorbent